2020
DOI: 10.18632/oncotarget.27830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isoform-specific HIF-1α and HIF-2α antisense oligonucleotides on tumorigenesis, inflammation and fibrosis in a hepatocellular carcinoma mouse model

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. For advanced HCC, there is still an unmet need for more effective therapeutic strategies. HCC is typically associated with hypoxia and the hypoxiainducible factor (HIF) regulatory pathway plays an important role in HCC development and progression. Therefore, we investigated the therapeutic potential of isoformspecific HIF-1α and HIF-2α antisense oligonucleotides (ASOs), along with their effect on the inflammatory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…As a final comment, one should note that the mentioned involvement of HIF2α activation in pro-fibrogenic progression of CLD has already led to the use in preclinical studies of specifically designed therapeutic strategies. The first study to be mentioned employed in vivo administration of isoform-specific HIF-1α and HIF-2α antisense oligonucleotides (ASOs) in a murine model of diethyl-nitrosamine (DEN)-induced CLD and HCC [ 133 ]. This study revealed that both the ASOs employed did not prevent but rather enhanced inflammation and fibrosis, suggesting that directly targeting HIF2α in the liver may not represent the right approach.…”
Section: Hif1α and Hif2α: Two Distinct Critical Players In Fibrogenic Cld Progressionmentioning
confidence: 99%
“…As a final comment, one should note that the mentioned involvement of HIF2α activation in pro-fibrogenic progression of CLD has already led to the use in preclinical studies of specifically designed therapeutic strategies. The first study to be mentioned employed in vivo administration of isoform-specific HIF-1α and HIF-2α antisense oligonucleotides (ASOs) in a murine model of diethyl-nitrosamine (DEN)-induced CLD and HCC [ 133 ]. This study revealed that both the ASOs employed did not prevent but rather enhanced inflammation and fibrosis, suggesting that directly targeting HIF2α in the liver may not represent the right approach.…”
Section: Hif1α and Hif2α: Two Distinct Critical Players In Fibrogenic Cld Progressionmentioning
confidence: 99%
“…However, which cells contribute to the TAM pool has only partly been unraveled. We and others showed that HCC is characterized by KC depletion and a simultaneous rise of MoMFs, at least in mice [ 60 , 362 , 363 ]. However, we also showed that, in addition to the widely accepted contribution of infiltrating MoMFs to the TAM pool in HCC, KCs also express markers that are typically associated with TAMs [ 128 ].…”
Section: Macrophages During Gut-liver Axis Disruption In Chronic Liver Diseasementioning
confidence: 99%
“…For example, DEN model is a commonly used model since it is effective in producing tumors with an incidence of 100% of the study subjects; this model generates fibrogenesis and loss weight in experimental animals and also allows the presence of inflammatory infiltrate and proinflammatory cytokines, yet a constant and consecutive weekly application of DEN is necessary for 15 weeks, starting from 5 weeks of age of the animals under study. It is important to mention that it is difficult to establish the onset of the appearance of carcinogenic damage and, therefore, the analysis of the events that occur in the early stages of the disease [ 41 ].…”
Section: Experimental Models For Hcc Researchmentioning
confidence: 99%
“…For example, DEN model is a commonly used model since it is effective in producing tumors with an incidence of 100% of the study subjects; this model generates fibrogenesis and loss weight in experimental animals and also allows the presence of inflammatory infiltrate and proinflammatory cytokines, yet a constant and consecutive weekly application of DEN is necessary for 15 weeks, starting from 5 weeks of age of the animals under study. It is important to mention that it is difficult to establish the onset of the appearance of carcinogenic damage and, therefore, the analysis of the events that occur in the early stages of the disease [41]. e CCl 4 model allows HCC implementation through fibrosis and cirrhosis generation and the first neoplastic lesions that would become part of adenomas and carcinomas in different tissues; this model also offers the advantage of analyzing genotoxic events at the hepatic level and liver fat accumulation as well as chronic progressive nephropathy.…”
Section: Experimental Models For Hcc Researchmentioning
confidence: 99%